Therapeutic mechanisms of polysaccharides in the management of rheumatoid arthritis: a comprehensive review - Liu, Wenlong; Kong, Youqian; Wang, Xiaoyu; Yang, Yuanyuan; Yan, Qi; Li, Zeguang (Frontiers in Immunology, 2025)
Rheumatoid Arthritis (RA) is a chronic autoimmune disease characterized by synovial inflammation and destruction of articular cartilage and bone, which seriously affects patients’ quality of life. In recent years, with the in-depth research on natural medicines, the application of polysaccharides in the treatment of RA has gradually gained attention due to their unique bioactive components and diverse pharmacological effects. Polysaccharides were reported to exert anti-inflammatory, antioxidant, immunomodulatory, and protective effects on cartilage and bone tissues. This review briefly introduces RA, its etiology and pathogenesis, and the different sources and structures of polysaccharides. It focuses on the mechanisms of polysaccharides in the alleviation of RA, mainly through the modulation of immune cell function, inhibition of inflammation, regulation of gut microbiota, promotion of bone formation and repair, and influence on related pathways. The aim of this review is to summarize the polysaccharides and their mechanisms of action in the alleviation of RA, with a view to providing new ideas for the clinical treatment of RA.